Studies on Gonococcus Infection X. Pili and Leukocyte Association Factor as Mediators of Interactions Between Gonococci and Eukaryotic Cells In Vitro - Swanson, John (1975)
Two independent gonococcal surface components, pili and leukocyte association factor, appear to mediate in vitro interactions of Neisseria gonorrhoeae with tissue culture cells and human peripheral blood leukocytes, respectively.